PHYSICAL QUALITY OF AN OXISOL UNDER AN INTEGRATED CROP-LIVESTOCK-FOREST SYSTEM IN THE BRAZILIAN CERRADO - Sousa Neto, Eurico Lucas de; Andrioli, Itamar [UNESP]; Almeida, Roberto Giolo de; Mota Macedo, Manuel Claudio; Lal, Rattan (Soc Brasileira De Ciencia Do Solo, 2014)
Soil physical quality is an important factor for the sustainability of agricultural systems. Thus, the aim of this study was to evaluate soil physical properties and soil organic carbon in a Typic Acrudox under an integrated crop-livestock-forest system. The experiment was carried out in Mato Grosso do Sul, Brazil. Treatments consisted of seven systems: integrated crop-livestock-forest, with 357 trees ha(-1) and pasture height of 30 cm (CLF357-30); integrated crop-livestock-forest with 357 trees ha(-1) and pasture height of 45 cm (CLF357-45); integrated crop-livestock-forest with 227 trees ha(-1) and pasture height of 30 cm (CLF227-30); integrated crop-livestock-forest with 227 trees ha(-1) and pasture height of 45 cm (CLF227-45); integrated crop-livestock with pasture height of 30 cm (CL30); integrated crop-livestock with pasture height of 45 cm (CL45) and native vegetation (NV). Soil properties were evaluated for the depths of 0-10 and 10-20 cm. All grazing treatments increased bulk density (rho(b)) and penetration resistance (PR), and decreased total porosity (f(t)) and macroporosity (f(ma)), compared to NV. The values of rho(b) (1.18-1.47 Mg m(-3)), f(ma) (0.14-0.17 m(3) m(-3)) and PR (0.62-0.81 MPa) at the 0-10 cm depth were not restrictive to plant growth. The change in land use from NV to CL or CLF decreased soil organic carbon (SOC) and the soil organic carbon pool (SOCpool). All grazing treatments had a similar SOCpool at the 0-10 cm depth and were lower than that for NV (17.58 Mg ha(-1)).
Keywords: agroforestry; soil organic carbon; multivariate analysis